Impact of Short-Duration Video Intervention to Improve Knowledge of Dental Malocclusion Among High School Students: Lessons from A Time-Constrained Study - Bahar, Armasastra; Amalia, Fitria Rizqy; Darwita, Risqa Rina; Ramadhani, Atik; Badruddin, Iwany Amalliah; Rahardjo, Anton (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: This study aimed to evaluate the effectiveness of a video-based educational intervention for improving knowledge of dental malocclusion among students at SMAN 39, Jakarta, and to examine the associations between knowledge levels and sociodemographic factors. Materials and Methods: A quasi-experimental design involving 159 students was employed. Data were collected via structured pre-test and post-test questionnaires assessing students’ knowledge of dental malocclusion. Statistical analyses included the Wilcoxon signed-rank test, Mann–Whitney U test, and Spearman correlation coefficient to examine associations between variables. Results and Discussion: All 159 participants completed both the pre-test and post-test. A statistically significant improvement in knowledge was observed following the intervention (p = 0.001). While sex, age, and socioeconomic status were not significantly associated with baseline knowledge, the post-intervention results indicated that female students, older age groups, and students from higher-income households demonstrated significantly greater knowledge retention (p-value < 0.05). Conclusion: Video-based interventions effectively enhanced student’s knowledge of dental malocclusion; however, the extent of improvement varied across sociodemographic groups. These findings suggest that sex, age, and socioeconomic status may influence educational outcomes. Future oral health education initiatives should consider these factors to increase the effectiveness and inclusivity of digital learning interventions.